Presacral Medulloepithelioma: Case Report and Literature Review. Issue 3 (April 2020) - Honnorat, Marion; Al-Karmi, Salma; Hawkins, Cynthia; Johnston, Donna; Gerstle, Ted; Schechter, Tal; Huang, Annie; Bouffet, Eric
Abstract : Medulloepithelioma is a rare early childhood tumor typically presenting in the intraocular region and neuroaxis. We report a rare case of a 2-year-old girl that presented with a peripheral medulloepithelioma in the presacral region. Examination of the tumor revealed that it lacked amplification of the 19q13.42 locus yet was positive for LIN28A. The patient was treated with intensive and high-dose chemotherapy as per 99703 protocol followed by complete surgical resection of the tumor and rapamycin maintenance and remains disease-free 5 years postinitial diagnosis. Ten previous cases were reported, including 5 patients who were alive disease free at the time of the publication. Optimal management of this rare condition is still controversial, particularly with regard to the respective role of chemotherapy and radiation.